Enterpreneurship platform through BICE 2017 / Zarul Azhar Nasir - Nasir, Zarul Azhar (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Department of Business Management of UiTM Perak Branch Tapah Campus had organized Business Innovation Competition and Exhibition (BICE) 2017. In general, the objective of this program was to promote entrepre-neurial spirit among the students of UiTM Perak Branch Tapah Campus particularly to those who are taking entrepreneurship course in the current semester. This program also provided a platform for students to highlight creative and innovative ideas in the production of business products. In order to achieve the objectives outlined, two main activities were carried out under this program, which were exhibition of entrepreneurial ideas and business talks.